Agrofuel policies in Brazil: paradigmatic and territorial disputes - Fernandes, Bernardo Mançano [UNESP]; Welch, Clifford Andrew; Goncalves, Elienai Constantino [UNESP] (Routledge Journals, Taylor & Francis Ltd, 2010)
The expansion of agrofuel crops challenges us to rethink policies, territories, human agency, and the paradigms used to explain them. In Brazil, policies supporting the expansion of agrofuel crops and the intensification of agrofuel production are reorganising rural land use and undermining some forms of participation in the capitalist and family modes of production. To reflect on this new reality, we study peasant movement reactions, proposals, and territorial disputes with agribusiness. Using the Pontal do Paranapanema region of São Paulo state as a case in point, the paper analyses territorial disputes between expanding sugarcane plantations and agrarian reform settlements as well as biodiesel production projects developed by the Landless Workers Movement (MST) and the Western São Paulo Federation of Settlement and Family Farmer Associations (FAAFOP). It also analyses the agrofuel policies of other peasant organisations, including Via Campesina. The production of agrofuels has changed the processes of land acquisition and use by both agribusiness and the peasantry, provoking new insights into the nature of territorial conflicts and thereby stimulating the need to revise perspectives on the agrarian question in Brazil.
Keywords: agrarian question; agrofuels; territory; MST; Via Campesina; CONTAG